The long run performance of initial public offering: Focused in Mesdaq market / Hilmie Shakilah Shukor - Shukor, Hilmie Shakilah (2007)
This study had focused on the long run performance of initial public offering in Malaysia from June 2002 to December 2006. This is analyzed by looking the monthly stock price on 48 IPO's companies that listed in Mesdaq Market of Bursa Malaysia. Bursa Malaysia Composite Index will be used as a benchmark in evaluating share price performance. The objective of this research is to determine the long term performance of IPOs. This in order to find out whether IPO is under perform or over perform the market for the long run. Buy and Hold Abnormal Return has been used to determine the long term performance of IPOs. According to the analysis for the period Jun 2002 to December 2006, it is indicated that Malaysia IPO did under perform the benchmark in such magnitude that this resulted on average in a negative long run performance for the entire sample period. The t-statistic shows that BHARs are not significant at the 5 % level. It is because due to subsequent long-run abnormal return that to be quite negative.